2020
DOI: 10.1111/medu.14296
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic sleep deprivation in residents: Cognition and stress biomarkers

Abstract: Objectives Insufficient sleep affects circadian hormonal profiles and inflammatory markers and may modulate attention, executive functioning and decision‐making. Medical professionals and specifically resident physicians, who are involved in long‐term nightshift schedules during their post‐graduate training, are prone to acute and chronic sleep deprivation and disruption, putting them at risk for making medical errors. The aim of the study was to evaluate the impact of chronic and acute‐on‐chronic sleep depriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 82 publications
2
27
0
Order By: Relevance
“…Cortisol increased after a night of TSD in all participants, consistent with some prior studies using healthy samples ( Leproult et al, 1997 ; Wright et al, 2015 ; Choshen-Hillel et al, 2021 ; Lamon et al, 2021 ), but not with others ( Åkerstedt et al, 1980 ; Vgontzas et al, 2004 ; Frey et al, 2007 ; van Leeuwen et al, 2009 ; Pejovic et al, 2013 ; Honma et al, 2020 ). Cortisol also decreased from TSD AM to TSD PM, reflecting its well-established, time-of-day profile ( Krieger et al, 1971 ; Czeisler et al, 1999 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Cortisol increased after a night of TSD in all participants, consistent with some prior studies using healthy samples ( Leproult et al, 1997 ; Wright et al, 2015 ; Choshen-Hillel et al, 2021 ; Lamon et al, 2021 ), but not with others ( Åkerstedt et al, 1980 ; Vgontzas et al, 2004 ; Frey et al, 2007 ; van Leeuwen et al, 2009 ; Pejovic et al, 2013 ; Honma et al, 2020 ). Cortisol also decreased from TSD AM to TSD PM, reflecting its well-established, time-of-day profile ( Krieger et al, 1971 ; Czeisler et al, 1999 ).…”
Section: Discussionsupporting
confidence: 91%
“…Although well investigated, the effects of sleep deprivation on cortisol, a hypothalamic–pituitary–adrenal (HPA) axis marker, and C-reactive protein (CRP), an inflammatory marker, remain inconsistent: some studies report no change in cortisol ( Vgontzas et al, 2004 ; Frey et al, 2007 ; van Leeuwen et al, 2009 ; Pejovic et al, 2013 ; Honma et al, 2020 ) or CRP ( Faraut et al, 2011 ; Irwin et al, 2016 ; Choshen-Hillel et al, 2021 ), while others report decreases in cortisol ( Åkerstedt et al, 1980 ) or CRP ( Frey et al, 2007 ; Baek et al, 2020 ), or increases in cortisol ( Leproult et al, 1997 ; Wright et al, 2015 ; Baek et al, 2020 ; Choshen-Hillel et al, 2021 ; Lamon et al, 2021 ) or CRP ( Meier-Ewert et al, 2004 ; van Leeuwen et al, 2009 ). Similarly, studies have found that both acute and prolonged stress increase cortisol ( Jönsson et al, 2010 ; Allen et al, 2014 ) and CRP ( Eraly et al, 2014 ; Kennedy et al, 2014 ), although other studies reported no change in CRP ( La Fratta et al, 2018 ; Szabo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“… 10 Specifically, sleep problems affect circadian hormonal profiles and inflammatory markers, and may damage executive function, attention and decision-making capacity. 11 …”
Section: Introductionmentioning
confidence: 99%
“…10 Specifically, sleep problems affect circadian hormonal profiles and inflammatory markers, and may damage executive function, attention and decision-making capacity. 11 Like many biological processes, sleep is associated with immunity and inflammation and changes in circulating immune cells. 11 Inflammation is a process by which the body responds to injury or infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation